A Novel Anti-bacterial, Histopathological and Immunomodulatory Effect of Lactobacillus Reuteri and Exopolysaccharide in Pneumonia Model - Likaa Mahdi (Journal of Global Pharma Technology, 2018)
Objective: The current study aimed to evaluate the antibacterial activity of exopolysaccharide (EPS) against multidrug resistant Klebsiella pneumoniae isolated from blood cultures in vitro and evaluate the potential antibacterial, histopathological and immunomodulatory efficacy of Lactobacillus reuteri and EPS against K.pneumoniae in-vivo. Materials and methods: purification and characterization of EPS produced from L.reuteri.BALB mice were injected with K. pneumoniae, and treated with either L. reuteri or EPS, bacteriological, histopathological and cytokine production were determined. Results: Antibacterial activity of purified EPS was higher than crude P<0.05. In-vivo L. reuteri and EPS demonstrate a significant decreasing in the number of bacteria in liver and spleen, while complete clearance of K. pneumoniae in lung comparing with control P<0.05 and accelerated recovery of the defense mechanisms against K. pneumoniae by inducing two types of cytokines. These cytokines would be involved in the improvement of the immune response and limiting the injury caused by infection. Succeeded to eradicate K. pneumoniae infection improves histological patterns of the lung, spleen and hepatic tissues. Conclucion: L. reuteri and EPS, they could be novel therapeutic agents for prevention and treatment of pneumonia infection and introduced as potential novel candidates that have to be subjected for more in vivo and application studies for treatment and control of resistant K. pneumoniae. Keywords: L. reuteri, Exopolysaccharide, Immunomodulatory, Antibacterial, K. pneumoniae.